1996
DOI: 10.1152/ajpendo.1996.271.6.e1021
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of rat Na+/Pi cotransporter-1 gene expression: the roles of glucose and insulin

Abstract: Cytosolic inorganic phosphate (P(i)) is important for glucose metabolism. It plays a role in homeostatic regulation of glucose by insulin and glucagon. Recently, we isolated two cDNA clones for rat Na+/P(i) cotransporter-1 (rNaPi-1) and demonstrated that they are expressed primarily in the rat liver and kidney. We now report that the expression of rNaPi-1 in these tissues is regulated by fasting and streptozotocin-induced diabetes. Using rat hepatocytes in primary culture, we also demonstrate that glucose and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Hence, these data suggest that PiT-1 and PiT-2 play an important role in basolateral P i uptake in rat liver. Although it has been suggested that NaPi-I serves to supply the great demand of P i in the liver required for the high level of intracellular glucose metabolism (26), the physiological role of NaPi-I as sodium-phosphate cotransporter remains unclear (42).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, these data suggest that PiT-1 and PiT-2 play an important role in basolateral P i uptake in rat liver. Although it has been suggested that NaPi-I serves to supply the great demand of P i in the liver required for the high level of intracellular glucose metabolism (26), the physiological role of NaPi-I as sodium-phosphate cotransporter remains unclear (42).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the regulation of the type II transporter by dietary P i and PTH was shown to differ between PSTs and PCTs (12,13). In contrast, insulin and glucose can affect the expression of the rat type I transporter (14).…”
Section: Vitamin D Is An Important Regulator Of Phosphate Homeostasismentioning
confidence: 98%
“…This glucose-dependent increase in rNa-P i 1 mRNA expression was independent of insulin, since it was observed in diabetic rats. In primary cell cultures from rat hepatocytes, high glucose concentrations (10-30 mmol/L) also increased rNa-P i type I mRNA (but not Ram-1 mRNA) expression, but only if insulin (10 nmol/L) was present in the medium (Li et al 1996). Since we have used a DME/F12 ''high glucose'' medium containing 25 mmol/L D-glucose, this might have induced the expression of Na-P i 1 in these primary cell cultures of MTAL cells.…”
Section: Expression Of Na-p I Type I In Mtal Cellsmentioning
confidence: 94%
“…In both rat kidneys and cultured hepatocytes, high glucose concentrations selectively upregulated Na-P i type I expression (Li et al 1996). In rat brain, BNP-1 (a Na-P i cotransporter belonging to the type I Na-P i cotransporter family) may be involved in brain energy metabolism (Ni et al 1995).…”
Section: Hypotheses On Na-p I 1 Activation During Ischemiamentioning
confidence: 99%